PEMBELAJARAN JARAK JAUH PADA KEPANITERAAN KLINIS PROGRAM STUDI PROFESI DOKTER DI RUMAH SAKIT PENDIDIKAN - Anugrahsari, Santi (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2021)
ABSTRACT Introduction: It is not easy to regulate the clerkship system for medical professional education clinics when continuing to the hospital during the pandemic (Covid-19) so that students can acquire knowledge and skills according to predetermined competencies. Objective: Describe Distance Learning (PJJ) of Clinical clerkship students (coass) in teaching hospitals during the pandemic. Methods: A descriptive study of Clinical Clerkship students who carried out online activities during the pandemic period at the Teaching Hospital. Results: There were 51 respondents from clinical clerkship education participants, as many as 84.31% of respondents graduated from academic education in 2019-2020, just carried out the 1-2 rotation stage 47.05%, long waiting for the pandemic 5-7 months experienced by 56.86 % of respondents, there were more students who did not experience difficulties in accessing the internet, and simply adapting to do PJJ. Less than 50% of the learning time provided is appropriate. Students are satisfied to receive learning time per day, student communication with clinical teaching lecturers is classified as useful, and scheduling of learning with clinical doctors is relatively easy. Respondents answered PJJ quite effectively, as much as 56.86%. Conclusion: The most prominent problem is the fulfillment of clinical clerkship competence in patients' interactions in teaching hospitals due to the pandemic. However, more than that, various efforts have been made by institutions that provide clinical medical education. Keywords: Clinical Clerkship - Teaching Hospital - Distance Learning - Doctor's Professional Study Program ABSTRAK Pendahuluan : Hal yang tidak mudah dalam mengatur sistem kegiatan kepaniteraan klinik pendidikan profesi dokter pada saat melanjutkan stase di rumah sakit selama masa pandemi (Covid-19) sehingga peserta didik dapat memperoleh pengetahuan dan keterampilan sesuai dengan kompetensi yang telah ditetapkan. Tujuan : Menggambarkan Pembelajaran Jarak Jauh (PJJ) peserta didik kepaniteraan muda (coass) di Rumah Sakit Pendidikan selama pandemi. Metode : Penelitian deskriptif terhadap peserta didik kepaniteraan muda yang melakukan kegiatan daring selama masa pandemi di Rumah Sakit Pendidikan. Hasil : Terdapat 51 responden dari peserta pendidikan kepaniteraan klinis, sebanyak 84,31% responden lulus dari pendidikan akademik di tahun 2019-2020, baru menjalankan stase 1-2 rotasi 47,05 %, lama menunggu pandemi 5-7 bulan di alami oleh 56,86% responden, lebih banyak peserta didik tidak mengalami kesulitan akses internet, dan beradaptasi cukup melakukan PJJ. Kurang dari 50 % Waktu pembelajaran yang diberikan sesuai, peserta didik puas menerima waktu pembelajaran per hari, komunikasi mahasiswa dengan dosen pendidik klinis tergolong baik, serta pengaturan jadwal pembelajaran dengan dokter klinis cukup mudah. Responden menjawab PJJ cukup efektif sebanyak 56,86%. Kesimpulan: Permasalahan yang paling menonjol adalah pemenuhan kompetensi kepaniteraan klinis dalam interaksi dengan pasien di RS Pendidikan dikarenakan pandemi. Namun daripada itu, berbagai upaya telah dilakukan oleh Instansi penyelenggara pendidikan kedokteran klinis. Kata kunci : Kepaniteraan Klinis – RS Pendidikan – Pembelajaran Jarak Jauh - Program Studi Profesi Dokter